DREPTUL LA PROPRIA IMAGINE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The Right to Own Image.The right to own image is not recent legal creation, at first, it is only known to us, humans, based on biblical assertions – The Book of Genesis, Chapter I, verses 26, 27; legal habits Such as the protection of dead person’s memory until today with the Convention for the Protection of Human Rights and Fundamental Freedoms – Art. 8, 10; Universal Declaration of Human Rights – art. 12 and other subsequent legal rules. The right to own image constitutes one of the essential foundations of a democratic society, where people are held to respect other people’s freedom of expression, without prejudice in any way of the dignity, honor, privacy of person, etc. and so, people must benefit from special protection. With exceptions, the right to own image should not obstruct truth in matters of legitimate public interest.